2021
DOI: 10.1186/s12944-021-01472-2
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent smoking and alcohol consumers had higher triglyceride glucose indices than either only smokers or alcohol consumers: a cross-sectional study in Korea

Abstract: Background The triglyceride glucose (TyG) index is a noninsulin-based marker for insulin resistance (IR) in general practice. Although smoking and heavy drinking have been regarded as major risk factors for various chronic diseases, there is limited evidence regarding the combined effects of smoking and alcohol consumption on IR. This study aimed to investigate the relationship between the TyG index and smoking and alcohol consumption using two Korean population-based datasets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…Elderly-onset T2DM patients have relatively preserved β-cell function and higher IR [14]. Furthermore, while previous studies have demonstrated a high prevalence of IR and T2DM in smokers and drinker [49], the univariate analysis in this study found that smoking was only associated with pre-DM but not T2DM, and that drinking was not associated with pre-DM and T2DM. The present study also found that the association of TG/HDL-C with pre-DM and T2DM was not affected by smoking and drinking status.…”
Section: Discussioncontrasting
confidence: 72%
“…Elderly-onset T2DM patients have relatively preserved β-cell function and higher IR [14]. Furthermore, while previous studies have demonstrated a high prevalence of IR and T2DM in smokers and drinker [49], the univariate analysis in this study found that smoking was only associated with pre-DM but not T2DM, and that drinking was not associated with pre-DM and T2DM. The present study also found that the association of TG/HDL-C with pre-DM and T2DM was not affected by smoking and drinking status.…”
Section: Discussioncontrasting
confidence: 72%
“…The study also verified that examined the association of TG/HDL-C with T2DM and pre-DM existed across different sex, age, smoking, and drinking statuses, as IR might changes with these factors [ 19 , 43 , 44 ]. Past studies have generally concluded that females exhibit more favorable metabolic risk profiles than males, including lower TG and higher HDL-C levels, and the association of dyslipidemia with DM appears to be stronger among males [ 45 ], middle-aged patients [ 46 ], and smokers and drinkers [ 47 ]. Conversely, when TG/HDL-C was used as a continuous variable in our study, it was associated with pre-DM and T2DM at different ages, sexes, smoking and drinking status, but stronger in females, people over 60 and those who do not smoke and drink alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly-onset T2DM patients have relatively preserved β-cell function and higher IR [ 14 ]. In addition, the relationship between alcohol consumption and IR T2DM remains controversial [ 47 ]. A meta-analysis evaluating the association between alcohol consumption and the risk of metabolic syndrome reported that compared with non-drinkers, very light drinkers were significantly associated with a reduction in the risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Baek [149] recruiting 10,568 Korean KNHANES registered adults and 9586 Korean KOICA registered adults in cross-sectional design with deriving retrospective patient records, demonstrated compared to no use of alcohol and smoking in KHANES participants those with smoking (OR:2.37), alcohol use (OR:3.09) and concurrent use (OR:4.59) had greater risk of having high TyG (Triglyceride Glucose) index, consistently also for KOICA registry smoking (OR:1.33), alcohol use (OR:1.42) and concurrent use (OR:1.94) associated with greater risk of high-TyG, moreover, in KOICA registry no regular exercise also posed greater odds of high-TyG (OR:1.26).…”
Section: Cac-development With Progressing Risk Factorsmentioning
confidence: 99%